The philosopher's toothache : embodied stoicism in Early Modern English drama - Sherman, Donovan (Evanston, Illinois : Northwestern University Press, 2022)
"Informed by work in both classical philosophy and performance studies, this book argues that Stoicism infused the theatrical culture of early modern England. Plays written during this period instruct audiences to cultivate their virtue, self-awareness, and creativity in keeping with Stoic practice"--
Introduction. More Things -- Dining with Lipsius -- We Know the World: Stoic Fate in Marston's Antonio Plays -- Acting Indifferently: Apatheia in Much Ado about Nothing -- Unbrace the Air: Stoic Cosmology in The Atheist's Tragedy -- Othello's Slave -- Conclusion: The Dust of the Humanities.
Includes bibliographical references and index.
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; Stoics in literature; Philosophy in literature; English drama -- Early modern and Elizabethan; Philosophy in literature; Stoics in literature; 1500-1600; Criticism, interpretation, etc